Dynamic Assessment Approach to Enhance the University EFL Students’ Ability on Listening to Learn - Nur Ekaningsih; Januarius Mujiyanto; Rudi Hartono; Issy Yuliasri (Universitas Negeri Semarang, 2022)
The University students’ problems in learning listening give an impact on students’ learning and achievement. This research objective is to scrutinize the role of Dynamic Assessment (DA) approach in enhancing the University students’ ability in listening to learn. Previous researchers argue that DA Approach motivates students’ critical thinking and activate students’ prior knowledge in listening comprehension class. By using a quasi-experimental design, an author wants to find out whether DA is effective or not in enhancing the students’ competence in listening class. The experimental and control class was designed to apply the treatment activities in listening to learn class. 40 participants of EFL students at private University in Semarang were divided into 20 in the experimental class and 20 for the control class. The data for investigation was taken from pre-test and posttest for both classes. DA Approach was applied in experimental and traditional approach was in control class. The SPSS used to analyze the data to see the descriptive analysis that is significance or not. Then, the result displayed based on SPSS tabulation that DA Approach was significant for EFL students in listening to learn ability.